2016
DOI: 10.3390/sym8090096
|View full text |Cite
|
Sign up to set email alerts
|

ANFIS-Based Modeling for Photovoltaic Characteristics Estimation

Abstract: Due to the high cost of photovoltaic (PV) modules, an accurate performance estimation method is significantly valuable for studying the electrical characteristics of PV generation systems. Conventional analytical PV models are usually composed by nonlinear exponential functions and a good number of unknown parameters must be identified before using. In this paper, an adaptive-network-based fuzzy inference system (ANFIS) based modeling method is proposed to predict the current-voltage characteristics of PV modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The artificial neural network was applied to civil engineering as early as 1989 [21], and then began to be widely welcomed in the fields of civil engineering, structural engineering, geotechnical environmental engineering, water resources engineering, and engineering geology. It is often used to solve problems such as concrete expansion prediction [22], saline soil frost heave prediction [23], soft rock strength prediction [24], composite material, and plastic hardening constitutive model identification, and so on [25][26][27]. The back propagation neural network (BPNN) is a sort of ANN which is widely applied at present.…”
Section: Introductionmentioning
confidence: 99%
“…The artificial neural network was applied to civil engineering as early as 1989 [21], and then began to be widely welcomed in the fields of civil engineering, structural engineering, geotechnical environmental engineering, water resources engineering, and engineering geology. It is often used to solve problems such as concrete expansion prediction [22], saline soil frost heave prediction [23], soft rock strength prediction [24], composite material, and plastic hardening constitutive model identification, and so on [25][26][27]. The back propagation neural network (BPNN) is a sort of ANN which is widely applied at present.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study showed that the ANN-models performed better than polynomial regression, multiple linear regression, analytical five-parameter single-diode models. In Mellit and Kalogirou (2011) and Bi et al (2016), the authors used adaptive neuro-fuzzy inference scheme (ANFIS) in an expert configuration PV power supply system. The results showed that the ANFIS-based modeling method gave a good prediction accuracy of 98% and performed better than the ANN counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, four statistical factors were introduced to assess the predictive power of the two models. The four evaluation factors are the coefficient of determination (R 2 ), the mean squared error (MSE), the mean absolute percent error (MAPE) and the mean absolute error (MAE) [31,43]. These factors can be calculated using Equations ( 18)- (21).…”
Section: Models Comparison Methodsmentioning
confidence: 99%
“…It applies the back-gradient method and the least squares algorithm, and uses the "If-Then" rule for management and constraints. In addition, with the help of the membership function, it completes nonlinear mapping of the data from the input to the output [30,31]. The structure of the ANFIS model is shown in Figure 3.…”
Section: The Adaptive Network-based Fuzzy Inference Systemmentioning
confidence: 99%